English, asked by 12344678910, 4 months ago

please give me answer of maths question 6​

Attachments:

Answers

Answered by HypersomniacAmbivert
207

\huge\bold{QUESTION}

♡If Secθ+Tanθ=m, Then Prove that

Secθ= =  \dfrac{ {m}^{2} + 1 }{2m}

\huge\bold{ANSWER}

Given:-

❥Secθ+Tanθ=m________(i)

To Prove:-

Secθ =  \dfrac{ {m}^{2} + 1 }{2m}

Proof:-

According To An Identity,

Sec²θ-Tan²θ=1________(ii)

We can Factorise Eqⁿ (ii)

[a²-b²=(a+b)(a-b)]

 =  > ( secθ +  tanθ)(secθ - tanθ) = 1 \\  \\  =  > m(secθ - tanθ) = 1

(Since, Secθ+Tanθ=m)

 =  > Secθ - Tanθ= \dfrac{1}{m} ________(iii)

❥From Eqⁿ (i) &(iii)

 \: \:  \:  \:  Secθ+Tanθ=m \\  + Secθ - Tanθ= \dfrac{1}{m}

_________________________

 =  > 2Secθ + 0=m +  \dfrac{1}{m}  \\  \\  =  > Secθ =  \frac{ {m}^{2}  +1 }{2m}

. ˙ . PROVED

ADDITIONAL INFORMATION

Some Basic Formulas

  • Sin²x+Cos²x=1

  • Sec²x-Tan²x=1

  • Cosec²x-Cot²x=1

  • sin(90°−x) = cos x

  • cos(90°−x) = sin x

  • tan(90°−x) = cot x

  • cot(90°−x) = tan x

  • sec(90°−x) = cosec x

  • cosec(90°−x) = sec x

  • sin(x+y) = sin(x)cos(y)+cos(x)sin(y)

  • cos(x+y) = cos(x)cos(y)–sin(x)sin(y)

  • sin(x–y) = sin(x)cos(y)–cos(x)sin(y)

  • cos(x–y) = cos(x)cos(y) + sin(x)sin(y)

  • sin¯¹ (–x) = – sin¯¹ x

  • cos¯¹ (–x) = π – cos¯¹x

  • tan¯¹ (–x) = – tan¯¹ x

  • cosec¯¹(–x) = – cosec¯¹ x

  • sec¯¹ (–x) = π – sec¯¹ x

  • cot¯¹(–x) = π – cot¯¹ x

\\ \\ \\

\; \: \: \; \; HOPE IT HELPS

Attachments:
Answered by shikhakumari8743
4

Answer:

\huge\bold{QUESTION}QUESTION

♡If Secθ+Tanθ=m, Then Prove that

Secθ== \dfrac{ {m}^{2} + 1 }{2m}=

2m

m

2

+1

\huge\bold{ANSWER}ANSWER

Given:-

❥Secθ+Tanθ=m________(i)

To Prove:-

❥Secθ = \dfrac{ {m}^{2} + 1 }{2m}Secθ=

2m

m

2

+1

Proof:-

According To An Identity,

❥Sec²θ-Tan²θ=1________(ii)

We can Factorise Eqⁿ (ii)

[a²-b²=(a+b)(a-b)]

\begin{gathered} = > ( secθ + tanθ)(secθ - tanθ) = 1 \\ \\ = > m(secθ - tanθ) = 1\end{gathered}

=>(secθ+tanθ)(secθ−tanθ)=1

=>m(secθ−tanθ)=1

(Since, Secθ+Tanθ=m)

= > Secθ - Tanθ= \dfrac{1}{m}=>Secθ−Tanθ=

m

1

________(iii)

❥From Eqⁿ (i) &(iii)

\begin{gathered} \: \: \: \: Secθ+Tanθ=m \\ + Secθ - Tanθ= \dfrac{1}{m} \end{gathered}

Secθ+Tanθ=m

+Secθ−Tanθ=

m

1

_________________________

\begin{gathered} = > 2Secθ + 0=m + \dfrac{1}{m} \\ \\ = > Secθ = \frac{ {m}^{2} +1 }{2m} \end{gathered}

=>2Secθ+0=m+

m

1

=>Secθ=

2m

m

2

+1

. ˙ . ❥PROVED

ADDITIONAL INFORMATION

❥Some Basic Formulas

Sin²x+Cos²x=1

Sec²x-Tan²x=1

Cosec²x-Cot²x=1

sin(90°−x) = cos x

cos(90°−x) = sin x

tan(90°−x) = cot x

cot(90°−x) = tan x

sec(90°−x) = cosec x

cosec(90°−x) = sec x

sin(x+y) = sin(x)cos(y)+cos(x)sin(y)

cos(x+y) = cos(x)cos(y)–sin(x)sin(y)

sin(x–y) = sin(x)cos(y)–cos(x)sin(y)

cos(x–y) = cos(x)cos(y) + sin(x)sin(y)

sin¯¹ (–x) = – sin¯¹ x

cos¯¹ (–x) = π – cos¯¹x

tan¯¹ (–x) = – tan¯¹ x

cosec¯¹(–x) = – cosec¯¹ x

sec¯¹ (–x) = π – sec¯¹ x

cot¯¹(–x) = π – cot¯¹

Similar questions